Pengaruh Model Think Pair Share (TPS) Berbantuan Media Tangsapan Terhadap Hasil Belajar Siswa Materi Saruan Panjang Kelas II SD Negeri 19 Merawang - Rede, Istiqomah Redeyati; Fitri Apriani; Sisi Pitriyana (JBES (Journal Basic Education Skills), 2024)
This research was motivated by the low learning outcomes of students in long-unit material. The causal factors are that students have difficulty understanding the concept of units of length, teachers rarely apply learning models, and the media itself is underutilized. The aim of this research is to determine the efficacy of the Think Pair Share (TPS) model in facilitating the acquisition of class II long unit material at SD Negeri 19 Merawang through the use of tangsapan media. Quantitative research uses a one-group pre-posttest design and a pre-experimental approach is used. Second grade students at SD Negeri 19 Merawang were selected for this research using a saturated sampling method. Data were analyzed using paired samples t-test for hypothesis testing and Shapiro-Wilk normality test. According to the data, the unit length material test has quite a large impact on pre-test and post-test activities. The results of the pretest normality test (0.079 > 0.05) and posttest normality test (0.203 > 0.05) show that the data follows a normal distribution. This proves that H0 is wrong and Ha is correct, the hypothesis test results are 0.00 < 0.05. Research data at SD Negeri 19 Merawang shows that the Think Pair Share (TPS) approach combined with the help of responsiveness has an effect on student learning outcomes in length unit material.